(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3JHJOF ef cJGH GdWGA , HGH GdWGA , hgh GdHGH GdPi cGf BNQ GdLRA GdChd ef GdfSNI faSgG s
(3BNQgG (B:s
(3ef HGH GdjGA hGdgeRI , bhdg (B: (3hGdjGdjI aJM Gdeje cbQGAI GdHGbjf ai Khdg (B: (3jG GHf Ce hjLhR EKHGJ GdCda hGdgGA hGdhba aJbhd jG GHf CeGg , aEf hUdJ MPaJ GdgGA , bGd CHh GdfLe jG HfJ geG dG Jdhei hGgLYi hGddg CYde HGdUhGH Je GdQHY GdQGHY efs
(3GdfSNI HgG MhGTs
(3HMhGTjgG JYdjbGJ hTQhMs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs